A Retrospective Evaluation of the Utility of Capsule Endoscopy and Double-Balloon Endoscopy in Crohn’s Disease - Masanao Nakamura; Yoshiki Hirooka; Osamu Watanabe; Takeshi Yamamura; Kohei Funasaka; Eizaburo Ohno; Hiroki Kawashima; Ryoji Miyahara; Hidemi Goto (Gastroenterology Research and Practice)
Background. Although the usefulness of capsule endoscopy (CE) and double-balloon endoscopy (DBE) for the evaluation of Crohn’s disease (CD) is established, their capabilities in the differential diagnosis of small bowel stenosis have not been sufficiently addressed. The present study therefore aimed to retrospectively determine the types of patients for whom CE and DBE would confer the most benefit. Patients and Methods. We retrospectively reviewed data from 185 patients with established CD. A change of treatment based on CE or DBE results or successful DBE balloon dilation was defined as clinically useful indication. We then analyzed the factors significantly related to useful and poor indications. Results. CE results were assessed as useful indications in 28 (45%) of 62 patients. Multivariate analysis demonstrated that positive CRP and low IOIBD score are factors significantly related to a useful indication. DBE results were recognized as useful indications in 118 (77%) of 153 patients. Multivariate analysis indicated small bowel stenosis and abdominal pain as factors significantly associated with useful indications. All patients with a poor indication on CE had small bowel stenosis. Conclusions. CE was most useful for patients in clinical remission with positive CRP and without stenosis, whereas DBE was useful for patients with symptoms of stenosis.